Adapting the Youth Novel "Sprout - From Lanky to Legendary" By Primož Suhodolčan Into Easy-To-Read Format And Responses of Test Readers to The Adaptation (Preučevanje otroške in mladinske književnosti, 2025)
This chapter is based on the findings of a doctoral dissertation titled Reading and Comprehension of Youth Literary Texts for Students With Speech and Language Disorders and Adaptation of Texts into Forms that are Easier to Read. The youth novel Sprout – From Lanky to Legendary by Primož Suhodolčan was chosen for the study due to its popularity among young readers and the challenges it poses for individuals with reading comprehension difficulties, primarily because of the author’s unique linguistic style. With the author’s permission, the entire novel was adapted into an easy-to-read format. Elementary school students with speech and language disorders (SLD) participated as test readers during the adaptation process. The aim was to facilitate understanding of the text for children and adolescents with SLD by employing alternative linguistic techniques. This chapter presents specific examples of the adaptations made and examines the responses of test readers to the modified text.